Bully/victim problems in Northern Ireland?s schools: Data from the 2000 and 2003 Young Persons? Behaviour and Attitude Surveys - MCGUCKIN, CONOR (My University, 2009)
Mc Guckin and Lewis (2003, 2006, 2008), Mc Guckin, Cummins, and Lewis (in press, under review a), and Mc Guckin, Lewis and Cummins (under review b) have reported that little is known about the nature, incidence and correlates of bully/victim problems in the Northern Ireland school system. The aim of the present study was to examine the prevalence of self-reported experiences of bully/victim problems among a representative sample of 7,223 11 to 16 year olds living in Northern Ireland who participated in the 2003 `Young Persons? Behaviour and Attitude Survey? (YPBAS: Northern Ireland Statistics and Research Agency [NISRA], 2003). Respondents were presented with three questions enquiring explicitly and three questions enquiring implicitly about bully/victim problems. Across other questions, respondents volunteered other salient information about personal experiences of bully/victim problems (i.e., through use of the `other? response option). Almost one fifth of all respondents (17.2%, n = 1,026) reported being a victim of bullying behaviour, and 8.1% (n = 492) reported that they had picked on or bullied another school pupil. Bully/victim problems also pervaded personal experiences of school meal times, sporting activities and perceptions of personal safety. These findings are placed within the context of previous findings.
Proceedings of the British Psychological Society
The British Psychological Society (Northern Ireland Branch) Annual Conference
IN_PRESS
Keywords: Education